The determinants of profitability : evidence from plantation industry in Malaysia / Nur Farahanis Abas - Abas, Nur Farahanis (2016)
The aim of this study is to examine the determinants of profitability for plantation industry in Malaysia where the determinants comprises of internal and external (macroeconomic) factors. Internal determinants such as liquidity and capital structure where the company itself has the control over these determinants while external determinants is like inflation where it cannot be controlled by the management of the company. Secondary data was collected from three (3) plantation companies in Malaysia starting from the year of 2005 2014. The financial ratios technique such as Current Ratio (CR) and Debt to Equity Ratio (DER) were applied to calculate the independent variables and linear was used to run the regression model. The data collected were from journals, articles, and websites. All the data that were collected will be run by using Eviews software program to obtain the results. For future studies, it is recommended that more sample size and determinant factors can be included in determining the effect on profitability of plantation companies in Malaysia